Failure of the fifth WTO Ministerial Conference in Cancun: a looming crisis in the multilateral trade system?: a discussion paper - Chetaille, Anne; Tavernier, Karine (Technical Centre for Agricultural and Rural Cooperation, 2003)
The failure of the WTO Ministerial Conference in Cancun has generated more fears that hopes for the future of the multilateral trade system...